LUPUS VASCULITIS - Desislava Tsvetanova; Ivelina Yordanova; Hristina Haidudova; Klimentina Gospodinova; Verka Pavlova; Maya Alexieva; Milen Karaivanov; Dimitar Gospodinov (Peytchinski Publishing, 2019)
Combination between Leucocytoclastic vasculitis and Subacute cutaneous lupus erythematosus has been only rarely reported in the literature. Pathological cutaneous lesions are presented by purpura, erythematous macules, urticarial, nodules and necroses.We present a 58-year-old woman with painful nodular lesions on the left thigh.The disease started in June 2015 with photosensitivity and psoriasiform rashes on the back. Pathological cutaneous changes affected lateral and dorsal surface of the left thigh. It was presented by painful, indurated in base, ulcerative plaques, with unclear borders and necrotic surface. There were no deviations from complete blood count and biochemistry. Immunological investigations revealed elevated levels of MPO(рАNCA) - 1.38 U/ml, antinuclear antibodies (ANA)- 134.1 U/ml, SS-A(Ro) antibodies - 233.7 U/ml CRP- 12.7mg/l. Urine analysis revealed positive protein results.Escherichia coli was isolated from microbiology testing. Histopathological result from ulcerative lesions from the left thigh of the patient revealed necrotizing leukocytoclastic vasculitis. The result from direct immunofluorescence microscopy of lesional skin corresponded to lupus erythematosus.The diagnosis lupus vasculitis was made. Systemic therapy with chloroquine phosphate, methylprednisolone, methotrexate was administered. Topical treatment included proteolytic enzyme in dressings and vacuum therapy with good effect.